Synthesis and evaluation of novel O-functionalized aminated chitosan derivatives as antibacterial, antioxidant and anticorrosion for 316L stainless steel in simulated body fluid - Nazly Hassan; Aisha Hendy; Asmaa Ebrahim; T.M. Tamer (Journal of Saudi Chemical Society)
Chitosan’s Schiff base derivatives are taking the attention of scientists as a promising biomaterial for various applications. In this study, O-functionalized aminated chitosan (O-F-Am-Ch) was coupled with 4,4-dimethyl amino-benzaldehyde and N-methyl-2-pyrrolidone to produce Schiff bases (I) and (II), respectively. The chemical and physical properties of the new derivatives were investigated by Fourier transform infrared (FT-IR) that show a significant band for C=C between 1400 and 1600 cm−1, thermal gravimetric analysis (TGA), which demonstrate an increase in the thermal stability of new derivatives than O-F-Am-Ch and scanning electron microscope (SEM) that indicates a slight increase in the rough structure of the surface. In addition, 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assays that examined the antioxidant properties of the new Schiff bases. The biocidal activity against four different bacterial strains [two gram-negative (Pseudomonas aeruginosa and Escherichia coli) and two gram-positive (Bacillus cereus and Staphylococcus aureus)] demonstrates significant improvement of the inhibition activity compare to O-F-Am-Ch with more activity against Gram-negative bacteria than that against gram-positive bacteria.As an implanted alloy, 316L stainless steel is used as a temporary biomaterial in different countries without any pretreatment. Our study focused on further improving the alloy features by investigating the protection efficiency of O-F-Am-Ch and the synthesized Schiff bases for the 316L stainless steel surface against corrosion in simulated body fluid (SBF). The corrosion inhibition of these compounds was investigated using two electrochemical methods (potentiodynamic polarization technique and electrochemical impedance spectroscopy). The results suggested the formation of self-assembled monolayers (SAMs) of the compounds under investigation. Furthermore, they demonstrated a considerable dose-dependent inhibiting corrosion of 316L stainless steel in SBF, whereas the inhibition efficiency exceeds 77% at 1000 ppm for the Schiff bases II. In conclusion, the tested derivatives show promising properties to refine stainless steel for implant applications.